Detection of Isim in Al-Qur'anic Verses using the Isim Marking Method and Creating Hyperlinks to Support the Quranpedia Website Project - Muhamad Jibril; Eko Darwiyanto; Moch Arif Bijaksana (STMIK Budi Darma, 2023)
This research aims to detect isim words containing